![image](https://tex.z-dn.net/?f=+%5Cfrac%7Ba%7D%7Bm%7D+-+%5Cfrac%7Bm%7D%7Ba%7D+%3D+%5Cfrac%7B%7Ba%7D%5E%7B2%7D+-+%7Bm%7D%5E%7B2%7D+%7D%7Bma%7D+%5C%5C+%5C%5C+ma+%3E+0+%5C%5C+a+%3C+m+%3D+%3E+%7Ba%7D%5E%7B2%7D+-+%7Bm%7D%5E%7B2%7D+%3C+0+%28%28a-m%29%28a%2Bm%29%3C0%29+%5C%5C+%5Cfrac%7B+%7Ba%7D%5E%7B2%7D+-+%7Bm%7D%5E%7B2%7D+%7D%7Bma%7D+%3C+0+%3D+%3E+%5Cfrac%7Ba%7D%7Bm%7D+%3C+%5Cfrac%7Bm%7D%7Ba%7D+)
0 \\ a < m = > {a}^{2} - {m}^{2} < 0 ((a-m)(a+m)<0) \\ \frac{ {a}^{2} - {m}^{2} }{ma} < 0 = > \frac{a}{m} < \frac{m}{a} " alt=" \frac{a}{m} - \frac{m}{a} = \frac{{a}^{2} - {m}^{2} }{ma} \\ \\ ma > 0 \\ a < m = > {a}^{2} - {m}^{2} < 0 ((a-m)(a+m)<0) \\ \frac{ {a}^{2} - {m}^{2} }{ma} < 0 = > \frac{a}{m} < \frac{m}{a} " align="absmiddle" class="latex-formula">